Alemania y el triángulo del litio: entre la diplomacia comercial y la difusión normativa - León González, Jaime; Aguirre, Juan Carlos (Si Somos Americanos, 2023)
The relationship between foreign policy, trade diplomacy and regulatory diffusion has attracted little academic interest with respect to international relations theory. Specifically, the way in which the attempt to apply international standards emanating from countries in the Global North to the nations of the Global South has been little studied by scholars. In this regard, this research explores the characteristics of the life cycle of standards at the international level and how these may have different effects on the territories where attempts have been made to locate them. In order to demonstrate this, we considered three case studies linked to the lithium triangle (Argentina, Chile and Bolivia) and German investments related to this metal. Both domestically and internationally, Germany has promoted the need to generate an energy transition based on the development of electro-mobility, through the promotion of trade diplomacy. However, in this process it has also encountered some local resistance. At the same time, the German state's efforts have generated paradoxes regarding the promotion of the energy transition and the protection of the environment and human rights in those territories where lithium is being extracted.
CRIS-Team Scopus Importer:2024-12-16
Keywords: energy transition; Germany; lithium triangle; regulatory diffusion